Evaluación de cuatro de abonos orgánicos con diferentes dosis en el cultivo de tomate (Lycopersicum esculentum mill) en la época seca en la zona de Quevedo. - Campi Mendoza, Jessica Piedad (2010)
This research was conducted from August to November 2010 during the dry season in fine "La María" property of the State Technical University Quevedo (UTEQ), located at Km 7 via Quevedo - Empalme province of Los Rios, coordinates 79 º 32 'west longitude and 01 º 06' south latitude, elevation of 120 meters above sea level. The objectives were to assess the effects of organic fertilizers (liquid and solid) in the tomato crop, identify the type and dose of organic fertilizer to improve the effectiveness of manure applied to the tomato crop, to establish the most appropriate dose of organic fertilizers show greater response than fruits of better trade dress and conduct economic analysis of the level of performance, cost of treatment. Material was used as the hybrid tomato seed Highway, studies such as organic fertilizers and dose factors "Biol Bokashi + legume-based (organic) + Humus Biol Based Dust (organic) + Bokashi Biol Based Dust ( organic), Humus + Biol legume-based (organic) complete fertilizer (10-30-10) + Stimufol (chemical) and dose: high, medium, low ", which formed 13 treatments. Design used was "completely randomized block with factorial arrangement 2 x 2 x 3 +1 in 3 repetitions. All variables were subjected to analysis of variance and tests (LSD) and Tukey's least significant difference at 95% probability to determine differences between means of factors and treatments. Plant height was assessed at 30, 45 and 60 days, flowering, length, diameter, fruit x plant, fruit weight and yield kg / ha. Analysis and interpretation of the results concluded: That the variables (almost all) did not differ as responses to fertilizers and dosage, and increased plant height at 60 days was obtained with the application of Bokashi + Biol dust in high doses exceeding 12.53 cm in the application of vermicompost + biol medium dose of dust that turned out to be smaller plants. The greatest number of fruits x plants was obtained with 9.97 + biol bokashi dust in high dose (500g +600 cc) and the fruits of greater weight were achieved with the low dose of worm humus fertilizer Biol powder + 40 g higher than the same fertilizer at